Stability Analysis Model of Plasmodium vivax from Anopheles in Human Infection using SIDR Population Compartment with Treatment RTS-S/AS01 Vaccine in Yogyakarta - -, Prihantini; Pratama, Yoga Bagas; Muhammad, Ammar (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
As the world population grows, many urban and rural area become the nest of malaria. Malaria is one of the most dangerous diseases for human beings and can be fatal. Malaria is caused by Plasmodium derived from the parasite protozoa class that multiplies in human blood cells. Malaria transmission occurs through the bite of Anopheles female mosquito that has been infected by Plasmodium vivax. The transmission process through the female Anopheles mosquito can be represented in mathematical model with the SIDR population approach. So far, research on mosquito breeding and spread of this type of disease only uses a mathematical model with the SIR population approach. Update from this research is to add populations of dormant species, populations that allow a person to positively heal or not. In this research the quantitative method is used that utilizes history data to create new model to be applied along with treatment that determined the RTS-S/AS01 vaccine does influence to prevention and reduction of infected population. The results obtained based on the model and graph is the treatment of RTS-S/AS01 vaccine which can reduce the number of infected population. Therefore, it can be concluded that the RTS-S/AS01 vaccine can prevent the spread of malaria disease. The objective of this study is to examine the spread of malaria and provide the solutions that malaria can be prevented from spreading using the RTS-S/AS01 vaccine.